Nuevos nidos de aves argentinas : Muscisaxicola rufivertex, Catamenia inornata, Sicalis olivascens y Carduelis crassirostris - Salvador, Sergio A. (1983)
The nests of 4 species of andean birds are described for the frrst time: Muscisaxicola rufivertex (parasitized by Molothrus bonariensis, also a first record), Catamenia inornata. Sicalis olivascens and Ozrduelis crassirostris . Descriptions of sites. materials, eggs and nestlings are included.